What is military history? - Morillo, Stephen (polity, 2006)
Presents a clear, readable introduction to a popular and growing field of history. * Concise chapters explain the fundamental features of the field, including: the history of military history; the key ideas and concepts that shape analysis of military activity; current controversies in the field; a look at the future of military history.